Burden Velocity Measurement in Cast Blasting Operations at Mount Thorley Mine Using POWERWAVE Face Velocity Radar - J J. Felice; W Klass; A T. Spathis (International Society of Explosives Engineers, 1992)
Cast blasting has become one of the most efficient ways to move waste rock in open cut coal mining. It is used at Mount Thorley Mine in conjunction with a dragline to move some of the overburden onto the spoil dump.